2011
DOI: 10.1080/10255841003766845
|View full text |Cite
|
Sign up to set email alerts
|

Computational structural modelling of coronary stent deployment: a review

Abstract: The finite element (FE) method is a powerful investigative tool in the field of biomedical engineering, particularly in the analysis of medical devices such as coronary stents whose performance is extremely difficult to evaluate in vivo. In recent years, a number of FE studies have been carried out to simulate the deployment of coronary stents, and the results of these studies have been utilised to assess and optimise the performance of these devices. The aim of this paper is to provide a thorough review of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 77 publications
(79 reference statements)
0
39
0
Order By: Relevance
“…6 Computational numerical methods are powerful tools used in the assessment of stent design and performance. 7,8 A number of studies have utilized the finite element method (FEM) to investigate the structural properties of stents and their biomechanical impacts on the coronary artery during stent expansion. [9][10][11][12][13][14] These studies mainly focus on research in which arterial tapering was not a factor, either through simplifying assumptions or by modeling specific, nontapered arteries.…”
Section: Introductionmentioning
confidence: 99%
“…6 Computational numerical methods are powerful tools used in the assessment of stent design and performance. 7,8 A number of studies have utilized the finite element method (FEM) to investigate the structural properties of stents and their biomechanical impacts on the coronary artery during stent expansion. [9][10][11][12][13][14] These studies mainly focus on research in which arterial tapering was not a factor, either through simplifying assumptions or by modeling specific, nontapered arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Others have used high levels of detail including full three-dimensionality and models for a complete balloon delivery system and a diseased artery with contact interactions between balloon, stent and tissue. 19,39 In addition to the review by Martin and Boyle, 31 Migliavacca et al 32 provided a succinct overview of early FEA studies of stent behaviour and performance. Notable among them was the two-dimensional study by Rogers et al 40 who focussed on the need to minimise vascular injury during stenting.…”
Section: Fea and Structural Optimalitymentioning
confidence: 98%
“…Since 1990, an ever increasing demand for endovascular stents has led to significant advancements in the field of analysis, modelling and design of stent implants (Chua et al, 2002;Duerig et al, 1999;Martin and Boyle, 2010;Petrini et al, 2004;Migliavacca et al, 2002;Lim et al, 2008;Lally et al, 2005;Timmins et al, 2007;Bedoya et al, 2006;Wang and Masood, 2006). The results of these studies have shown that besides mechanobiological factors, the geometry and typology of a stent are crucial aspects governing the device function.…”
Section: Introductionmentioning
confidence: 95%